Alkali–silica reaction in plain and fibre concretes in field conditions - Giaccio, Graciela Marta (2019)
This paper presents an experimental study on the effects of alkali–silica reaction (ASR) in concrete blocks placed outdoors, exposed to weather conditions. To promote different reaction kinetics and damage levels, the size of the reactive aggregates, the alkali content and incorporation of different fibre types (steel, polymer) were the variables considered. Expansions, crack patterns and air permeability were monitored for more than 3 years. In addition, standard expansion, compression and flexion tests were performed. The volume of concrete involved in ASR enhances the development of expansions and cracking; in the blocks different expansions were measured in vertical or horizontal directions and important cracks were observed. While the prisms expansions were attenuated after the first 12 months, in the blocks the damage by ASR continues growing for more than 3 years. Although the incorporation of macrofibers does not inhibit the development of ASR, it led to benefits such as reduction in cracking and deformations.